Spatialising university reform: Between a centre and a periphery in contemporary Finland. Issue 1 (1st March 2019) - Trifuljesko, Sonja
Abstract : This article investigates contemporary attempts to reform the institution of the university according to neoliberal ideological influences and oppositions to them. It employs Doreen Massey's concept of space to focus on relations and separations made in the process. My ethnography of the University of Helsinki's 375th anniversary celebration, which turned into a public spectacle of various visions of higher education, constitutes the main empirical material. Finland's ambivalent position in the world renders the spatial work of forging connections and disconnections particularly conspicuous. It enables specific neoliberal aspirations (such as to be among 'the world's best universities' amidst global competition) to become very strong but also allows additional trajectories, like the one about higher education as public goods, to present themselves as legitimate alternatives. The centre-periphery relations are therefore critical sites for analysing the contemporary university transformation, since they appear to be key drivers of the reform but also the primary source of resistance to it.